Knowledge modelling for contract disputes and change control - Wang, Chen; Yap, Jeffrey Boon Hui; Wood, Lincoln Christopher; Abdul-Rahman, Hamzah (Taylor & Francis, 2019)
The construction industry involves many participants with different perspectives and requirements. Contracts can provide significant value, and yet ineffective contract management frequently leads to disputes. In practice, contracts are hardly reviewed, and contract management is limited. This study aims to investigate how firms can improve their internal processes relating to knowledge management (KM) through effective contract management to aid construction practitioners in managing contract disputes and changes. Using a questionnaire survey and a workshop involving experienced industry practitioners and researchers, the findings reveal that project- and individual-level implementation of KM processes is stronger than at the organizational level, and also there are substantial human resources (HR) practices that support contractual KM. Workshop participants believe efficient and effective KM can minimise losses from contract changes and disputes. A construction contract management process framework, a 19-step benchmarking model for contract management and a construction planning checklist for contractors are proposed. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.